Underestimating the benefits of marine protected areas for the replenishment of fished populations. Issue 7 (2nd July 2019) - Marshall, Dustin J; Gaines, Steven; Warner, Robert; Barneche, Diego R; Bode, Michael
Abstract : Marine protected areas (MPAs) are important tools for managing marine ecosystems. MPAs are expected to replenish nearby exploited populations through the natural dispersal of young, but the models that make these predictions rely on assumptions that have recently been demonstrated to be incorrect for most species of fish. A meta‐analysis showed that fish reproductive output scales "hyperallometrically" with fish mass, such that larger fish produce more offspring per unit body mass than smaller fish. Because fish are often larger inside MPAs, they should exhibit disproportionately higher reproductive output as compared to fish outside of MPAs. We explore the consequences of hyperallometric reproduction for a range of species for population replenishment and the productivity of exploited species. We show that the reproductive contribution of fish inside MPAs has been systematically underestimated and that fisheries yields can be enhanced by the establishment of reservoirs of larger, highly fecund fish.